The Quality of the Scientific English Used in the Sinta Indexed Journal Articles in Indonesia: A Content Analysis - Sukur, Silvester Goridus; Mina, Yustina (Universitas Pendidikan Mandalika, 2024)
Quality English becomes one of the vital requirements to meet the standard quality of scientific journal articles including SINTA-indexed journal articles. Unfortunately, as seen from the articles accessed by the researcher to get related literature, the article writers fail to use quality English in their articles. This failure may lead to readers’ misunderstanding of the article content. This research aims to uncover and analyze to what extent the quality of English is in the SINTA-indexed journal articles published in Indonesia. The data of this content analysis were collected by purposively choosing thirty articles published in the SINTA 3, SINTA 2, and SINTA 1 journals published in Indonesia in the last two years. This research, conducted from January to July 2023, used the content analysis method. To process and analyze the data, NVivo 14 was used. The thirty articles were imported into NVivo 14 and coded inductively to get the themes needed according to the objective of this research. To get the research trustworthiness, the Kappa statistical reliability test in NVivo 14 was used. The results of the Kappa statistical reliability test showed that the value of the reliability agreement level of data was > 0.75, which proved that it was categorized as excellent. The result of this research is The thirty articles still contain English errors, which make the meaning of the sentences and ideas in the articles difficult to comprehend. The SINTA-indexed articles should be properly reviewed in terms of both their content and their English usage.